2021
DOI: 10.1111/asj.13621
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FSH treatment and withdrawal during proestrus on uterine proliferation and steroid hormone receptor expression in beef heifers

Abstract: To determine the effects of Follicle Stimulating Hormone (FSH) treatment and subsequent withdrawal on uterine proliferation and estrogen receptor (ESR), Brahman crossbred heifers (n = 12) were twice daily injected with FSH (4, 3, and 2 mg/injection) on Days 17–19 of the estrous cycle (FSH 3 days) and (4 and 3 mg/injection) on Days 17–18 (FSH 2 days) and withdrawal with saline on Day 19 and (4 mg/injection) on Day 17 (FSH 1 day) and withdrawal with saline on Days 18–19. Uterine tissue was subjectively collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…During the follicular phase (proestrus-estrus), it was reported an increase in the number of estradiol receptors α (ERα) in three parts of the uterus (Zeng et al, 2017;Perry et al, 2021). The increase in plasma E2 concentrations in the circulation and the increasing existence of Erα will cause the lengthening of uterine glands, followed by the production of estrus mucus by ciliated epithelial cells of the endometrium and secretory cells (Bunma et al, 2021). The increase in the thickness of the stratum functional and the activity of the other uterine glands during the estrus phase is a direct effect of the high increase in E2 synthesis in the GC.…”
Section: Discussionmentioning
confidence: 99%
“…During the follicular phase (proestrus-estrus), it was reported an increase in the number of estradiol receptors α (ERα) in three parts of the uterus (Zeng et al, 2017;Perry et al, 2021). The increase in plasma E2 concentrations in the circulation and the increasing existence of Erα will cause the lengthening of uterine glands, followed by the production of estrus mucus by ciliated epithelial cells of the endometrium and secretory cells (Bunma et al, 2021). The increase in the thickness of the stratum functional and the activity of the other uterine glands during the estrus phase is a direct effect of the high increase in E2 synthesis in the GC.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the FSHR is detected in gonadal tissues (specifically, granulosa and Sertoli cells); however, FSHR can also be found in extra-gonadal tissues of reproductive tract [21][22][23]. In this context, it has been demonstrated that in ruminant and human species, FSH affects uterine functions by changes in endometrium transcriptome, vascular density and endometrial morphology [24][25][26][27][28]. In pigs, the presence of FSH receptor in endometrium of prepubertal gilts was recently described [22,29], evidencing an extra-gonadal action of FSH in this specie.…”
Section: Introductionmentioning
confidence: 99%